Functional activity of human sodium/iodide symporter in tumor cell lines - Petrich, T.; Knapp, W.H.; Pötter, E. (Nuklearmedizin - NuclearMedicine, 2003)
Aim: The sodium/iodide symporter (NIS) actively transports iodide into thyrocytes. Thus, NIS represents a key protein for diagnosis and radioiodine therapy of differentiated thyroid cancer. Additionally, in the future the NIS gene may be used for cancer gene therapy of non-thyroid-derived malignancies. In this study we evaluated the functionality of NIS with respect to iodide uptake in a panel of tumor cell lines and compared this to gene transfer efficiency. Methods: A human NIS-containing expression vector and reporter-gene vectors encoding ß-Galactosidase- or EGFP were used for transient transfection of 13 tumor cell lines. Following transfection measurements of NIS-mediated radioiodide uptake using Na125I and of transfection efficiency were performed. The latter included ß-Galactosidase activity measurements using a commercial kit and observation by fluorescence microscopy for EGFP expression. Results: In contrast to respective parental cells, most NIS-transfected cell lines displayed high, perchlorate-sensitive radioiodide uptake. Differences in radioiodide uptake between cell lines apparently corresponded to transfection efficiencies, as judged from reporter-gene assays. Conclusion: With respect to iodide uptake we provide evidence that NIS is functional in different cellular context. As iodide uptake capacity appears to be well correlated to gene transfer efficiency, cell type-specific actions on NIS (e. g. post-translational modification such as glycosylation) are not inhibitory to NIS function. Our data support the promising role of NIS in cancer gene therapy strategies.
Keywords: Sodium/iodide symporter; cell culture; cancer